study for Evalution of Efficiency the commercial Influenza vaccines used with different vaccination programs. - Shiema Abid-Jabber; Nafea S.Jasim (Al-Qadisiyah Journal of Pure Science, 2018)
This study was planned to evaluate types of  inactivated  influenza vaccines in poultry field in  Iraq to reduce high incidence  outbreaks  of  disease to minimize high ecomoical losses in  broiler and  layers . the efficacy of vaccines  on immune response was evaluated depending  on indirect immune sorbent assay (ELISA) test at  (18,25,32,40) days of  age in experiment  consisting  of 800 chicks .The fifteen of chicks were selected randomly for maternal  immunity at 4 day of age , and  thirty â€“ five of chicks were left as acontrol  group , the rest of chicks were  divided into  five  groups  each group contains  ( 150) chicks of  broiler , the  first group was  vaccinated  by in activated  influenza + NDvaccine from intervet company ,the second group was vaccinated in activated  influenza + NDvaccine from merial company , the third group was vaccinated by inactivated  influenza + NDvaccine from vatro company ,while  the forth group was vaccinated by inactivated  influenza from izo company  , and the  fifth group was  vaccinated by  inactivated  influenza + ND from IZO company too , each company divided into five  subgroups , the subgroups  3, 4, 5 were vaccinated  with attenuated live  vaccines  of Newcastle  disease and  infections bronchitis. All vaccinated groups with influenza vaccines  were  vaccinated with IBD vaccine at (12) day of age .The results revealed high significant titer of  immune response  in the vaccinated  groups  comparison with  control group , and results showed significant  titer of  immunity  response in  subgroups , 2, 4 comparison  with  other  subgroups . the  influenza vaccine  from intervet  company  showed immune response more  than  other vaccines